Optically controlled liquid flow in initially prohibited elastomeric nanocomposite micro-paths - Francesca Villafiorita-Monteleone; Elisa Mele; Gianvito Caputo; Fabrizio Spano; Salvatore Girardo; P. Davide Cozzoli; Dario Pisignano; Roberto Cingolani; Despina Fragouli; Athanassia Athanassiou (2012)
The significant increment of TiO2 surface wettability upon UV irradiation makes it a promising component of materials or systems with tunable surface wetting characteristics. This remarkable property of TiO2 is retained in the nanocomposite materials developed for this work, which consist of the elastomer PDMS enriched with organic-capped nanorods of TiO2. In particular, the nanocomposites demonstrate a surface transition from a hydrophobic state to a hydrophilic one under selective pulsed UV laser irradiation. This wettability change is reversible, with the hydrophobic character of the nanocomposites being fully recovered after a couple of days of samples storage in moderate vacuum. The hydrophobic-to-hydrophilic transition and recovery can be repeated tens of times on the same sample without any apparent fatigue. As verified by XPS and AFM analysis, the wettability enhancement is exclusively attributed to the TiO2 nanorods exposed on the nanocomposite surface. The tuning of the surface wettability properties of the PDMS/TiO2 materials, together with the easy processability of this elastomer, opens the way to the realization of microfluidic devices with controlled liquid flow. We demonstrate the potentiality of such systems by fabricating microfluidic channels with walls of PDMS and PDMS/TiO2 nanorods composite materials. The combination of the used geometry with the hydrophobic character of both the pure and nanocomposite PDMS prohibits the penetration of water in their developed microchannels. After UV irradiation, water penetration is allowed inside the irradiated nanocomposite microfluidic channels, whereas it is still forbidden after the irradiation of the bare PDMS microchannels, revealing the essential role of the TiO2 nanofillers.